2011
DOI: 10.1016/j.buildenv.2011.04.019
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on climate responsive design strategies of vernacular housing in Vietnam

Abstract: Energy conservation issues and environmental problems in recent years have increased interest in traditional architecture which is well known for its energy saving designs. This paper thoroughly investigates vernacular housing designs and evaluates on the aspect of building physics. A new research methodology which is adapted to the natural and social context of Vietnam was proposed and applied. The process was carried out step by step, including: climate zoning, systematic analysis, in-situ survey and buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 14 publications
2
92
0
4
Order By: Relevance
“…Poor building design implies high energy demand for cooling and heating [15], while the bioclimatic design of buildings can improve their thermal performance. Bioclimatic design of buildings under hot and humid conditions has been studied in various papers, which provide interesting recommendations [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Poor building design implies high energy demand for cooling and heating [15], while the bioclimatic design of buildings can improve their thermal performance. Bioclimatic design of buildings under hot and humid conditions has been studied in various papers, which provide interesting recommendations [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to use vernacular designs to provide comfortable conditions, successful examples of which are found, for instance, in Vietnam (126) and India (127). Another is to allow natural ventilation, with the use of part-time and partial-space indoor climate conditioning, using mechanical systems for the remaining needs only when passive approaches cannot meet comfort demands.…”
Section: Demand-side Options For Multiple-objectives-based Developmentmentioning
confidence: 99%
“…The simulation results of the energy models suggested that considering traditions seen in ancient vernacular architecture as an approach to improving building energy performance is a worthwhile endeavor and a scientific guidance can help enhance the performance. In the study conducted by Nguyen et al [25], six old houses in rural and urban areas in Vietnam, were investigated to understand the climatic design strategies employed and their effectiveness in maintaining human comfort and health. The results of this study indicated that vernacular housing in Vietnam is creatively adapted to the local natural conditions and uses various climate responsive strategies.…”
Section: Energy Performance Of Vernacular Buildingsmentioning
confidence: 99%